Highly specific determination of IDH status using edited in vivo magnetic resonance spectroscopy. Issue 7 (6th November 2017) - Branzoli, Francesca; Di Stefano, Anna Luisa; Capelle, Laurent; Ottolenghi, Chris; Valabrègue, Romain; Deelchand, Dinesh K; Bielle, Franck; Villa, Chiara; Baussart, Bertrand; Lehéricy, Stéphane; Sanson, Marc; Marjańska, Małgorzata
Abstract: Background: Mutations in the isocitrate dehydrogenase ( IDH ) enzyme affect 40% of gliomas and represent a major diagnostic and prognostic marker. The goals of this study were to evaluate the performance of noninvasive magnetic resonance spectroscopy (MRS) methods to determine the IDH status of patients with brain gliomas through detection of the oncometabolite 2-hydroxyglutarate (2HG) and to compare performance of these methods with DNA sequencing and tissue 2HG analysis. Methods: Twenty-four subjects with suspected diagnosis of low-grade glioma were included prospectively in the study. For all subjects, MRS data were acquired at 3T using 2 MRS methods, edited MRS using Mescher–Garwood point-resolved spectroscopy (MEGA-PRESS) sequence and a PRESS sequence optimized for 2HG detection, using a volume of interest larger than 6 mL. IDH mutational status was determined by a combination of automated immunohistochemical analysis and Sanger sequencing. Levels of 2HG in tissue samples measured by gas chromatography–mass spectrometry were compared with those estimated by MRS. Results: Edited MRS provided 100% specificity and 100% sensitivity in the detection of 2HG. The 2HG levels estimated by this technique were in line with those derived from tissue samples. Optimized PRESS provided lower performance, in agreement with previous findings. Conclusions: Our results suggest that edited MRS is one of the most reliable tools to predict IDH mutation noninvasively, showing high sensitivity and specificity for 2HG detection. Integrating edited MRS in clinical practice may be highly beneficial for noninvasive diagnosis of glioma, prognostic assessment, and treatment planning.